PERAN PROGRAM KEAKSARAAN DASAR DALAM PERSPEKTIF PEREMPUAN DI PKBM LOMBOK TENGAH - Rahmat Syah; Ikhsanudin; Daddy Darmawan (Direktorat Pendidikan Masyarakat dan Pendidikan Khusus, Direktorat Jenderal PAUD, Pendidikan Dasar, dan Pendidikan Menengah, 2021)
Abstract: This study analyzes how the basic literacy education program (KD) is implemented from a feminist point of view. Through interviews, observations, and document analysis the researcher provides an overview of women's perceptions of the importance of basic literacy education. Data collection by purposive sampling was followed by the snow ball technique, in which the researcher visited the key informant at the research location, then continued with other informants based on the first informant's instructions on who the subjects should be contacted. Observations show that the majority (almost all) of active KD participants in Central Lombok are women (housewives). Based on the results of interviews and document analysis, it is known that there is a development in the ability and confidence of women who participate in KD activities, especially in daily activities and active participation in community social activities. This condition needs to be followed up with a sustainable literacy program accompanied by a women's empowerment program in the field. In order to support the implementation of the program, a more in-depth study is needed to produce guidelines for implementing literacy programs for women's empowerment so that women's empowerment and literacy programs are carried out in accordance with the culture that develops in the community. Abstrak: Penelitian ini menganalisis bagaimana program pendidikan keaksaraan dasar (KD) terlaksana dari sudut pandang feminismis. Melalui wawancara, pengamatan, dan analisis dokumen peneliti memberikan gambaran persepsi perempuan terhadap pentingnya pendidikan keaksaraan dasar. Pengambilan data secara purposive sampling diikuti juga oleh teknik snow ball yakni peneliti mendatangi informan kunci pada lokasi penelitian, kemudian dilanjutkan dengan informan lainnya atas petunjuk informan pertama tentang siapa saja subjek yang harus dihubungi. Hasil pengamatan menunjukan bahwa mayoritas (hampir semua) peserta KD aktif di Lombok Tengah adalah perempuan (Ibu Rumah Tangga). Berdasarkan hasil wawancara dan analisis dokumen, diketahui adanya perkembangan kemampuan dan kepercayaan diri perempuan yang mengikuti kegiatan KD terutama dalam kegiatan sehari-hari dan keaktifan partisipasi dalam kegiatan sosial masyarakat. Kondisi ini perlu ditindaklanjuti dengan program literasi berkesinambungan diiringi dengan program pemberdayaan perempuan di lapangan. Dalam rangka mendukung keterlaksanaan program tersebut, diperlukan kajian lebih mendalam untuk menghasilkan pedoman pelaksanaan program literasi untuk pemberdayaan perempuan sehingga program pemberdayaan dan literasi perempuan terlaksana sesuai dengan budaya yang berkembang di masyarakat.